(untitled) (Iter, 2022)
We maintain in accord with Heraclitus that beauty is a complex phenomenon and holds many levels of realization. Thus. we recognize a strictly human level. where aesthetic experience properly is realized. although there are some conditions wich allow establish diferences in this level of experience. Nevertheless. we also agree with He rae i tus. in regard to consider parí of the human aesthetic experience permiting the acknowledgment of a kind o f transcendent aesthetic connecting our perception and experience to a phisical level of reality. even more, with one metaphisical.